Overview of Knowledge, Attitude and Behavior of Pregnant Women in Self Monitoring of Fetal Movement - Nafisah, Nadila Zahra; Widiasih, Restuning; Mamuroh, Lilis (Indonesian Journal of Nursing and Health Sciences, 2025)
Fetal movement monitoring is one of the most important things to assess fetal well-being which can be done independently by pregnant women. However, studies on the ability of pregnant women to conduct self-monitoring of fetal movements were still limited. Objective: The purpose of this study was to determine the description of knowledge, attitude and behavior of pregnant women in self-monitoring of fetal movements in Sukawening District, Garut. This study used secondary data obtained from the main research entitled "Fetal Movement Counting Model: Efforts to Prevent Fetal Death Through Self-Monitoring by Pregnant Women" and with a quantitative descriptive design method. The sample in this study were 136 data on knowledge, attitude and behavior of pregnancy women in self-monitoring fetal movements. The instrument has been tested for construct validity and reliability by the principal researcher. The data analyzed univariately. Knowledge is categorized into good, enough, and less. Attitude is categorized into supportive and non-supportive. Behavior is categorized into positive and negative. The results indicated that pregnant women have less knowledge, supportive attitude, and positive behavior towards monitoring fetal movement.